(untitled) (Bangladesh Journal of Medical Science, 2023)
Teledentistry is an amalgamation of dentistry and telecommunication where the clinical information is exchanged between the patient/ caregiver with the dentist from a remote distance. The role of teledentistry came into spotlight in the pandemic Covid 19 era. This proved to be the safest method to provide health care assistance in preventing the disease transmission was cost effective and also formed a bridge between the rural and urban communities. It also helps in telediagnosis and formulation of treatment in dental emergenices. Teledentistry has improved a lot in the recent times due to advent of smart phones, widespread internet connectivity and video conferencing applications. Teledentistry could provide hassle free consultations as well the patient history can be stored in the data base for a longer period of time. This review highlights the origin, its applications, drawbacks and its role in the covid 19 and lock down phase. Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.52-57